ANALISIS KEPEMIMPINAN PEMERINTAHAN (STUDI KEPEMIMPINAN TRIYONO BUDI SASONGKO SEBAGAI BUPATI PURBALINGGA PERIODE 2000-2010) - Insan Azzamit; Fitriyah .; Teguh Yuwono (Journal of Politic and Government Studies, 2016)
The system of regional autonomy provided the authority to manage the affairs of their own region. Therefore, the strategic position of government leaders are important. Besides that, its also important if a regent capable and competent on leadership and government science. That matter related to the discussion of head region, Purbalingga Regent, Triyono Budi Sasongko which is famous as the name of “brillian regent” and one of the chief areas that managed to bring great changes to the area led. So, this journal made for analyze the government's leadership Triyono Budi Sasongko as Purbalingga Regent period 2000-2010. The method used is a qualitative research, a case study approach. The research instrument with interviews, observation and documentation study conducted on the sources of information were selected using certain considerations (purposive sampling) and the resources derived from the government sector, publik sector, and private sector related research problems. The results of the analysis of the government's leadership Triyono Budi Sasongko in the period 2000-2010 led Purbalingga: There are the influence of the leaders in creating effective government leadership. It can be seen from the pattern of leadership, leadership styles, as well as the determinants of efectivity leadership. Leadership that was close to the people, as well as a mix between leadership style transformatinal leadership with primal leadership which are capable of being thrust to boost publik participation in regional development so that the independence of the system in the form of community empowerment can be achieved. The study also found that the style of leadership, the ability of the leader personally into internal factors and political support, government administration, as well as the quality policy of external factors in stimulating the effectiveness of the government's leadership. Recommendations are given to the regional head that the pattern and style of leadership trasnformational and primal should be able continue to developed, and the head of each region should be able to accommodate the interests of various sectors, which are the government and the society,to create the effectiveness of the government's leadership. Keywords: Government Leadership, Political Leadership, Leadership Style, Leadership Effectiveness, Regional Head